Biodegradable hot melt adhesive comprising maleated PBAT and manufacturing method thereof

KR103031715B1Active Publication Date: 2026-10-13KYUNGPOOK NAT UNIV IND ACADEMIC COOP FOUND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020240098547
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2026-10-13
Estimated Expiration
2044-07-25

Smart Images

  • Figure 112024081167474-PAT00001_ABST
    Figure 112024081167474-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a biodegradable hot melt adhesive comprising a PBAT resin with excellent biodegradability and maleated PBAT prepared by grafting maleic acid onto PBAT using maleic acid and an initiator, and a method for manufacturing the same. Since the hot melt adhesive according to the present invention possesses improved adhesive strength while maintaining biodegradability almost similar to that of PBAT, it can be used as a hot melt adhesive for products requiring biodegradability, such as packaging paper and packaging containers containing biodegradable resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an eco-friendly hot melt adhesive that does not contain a solvent, possesses excellent biodegradability, and has excellent adhesive strength, making it easily applicable to various products, and a method for manufacturing the same. In particular, it relates to a hot melt adhesive manufactured by grafting maleic acid onto a PBAT resin with excellent biodegradability, and a method for manufacturing the same. Background Technology

[0002] Polymers are materials used for a wide variety of applications due to their excellent physical properties at a relatively low cost compared to other materials. Consequently, the production volume of polymers is increasing every year, with petroleum-derived polymers such as PP, PE, PS, and PMMA accounting for the majority of commonly used polymers.

[0003] Since petroleum-derived polymers require a very long time to decompose naturally, the amount of accumulated waste increases to an unmanageable level, becoming a major cause of environmental pollution today. Consequently, extensive research is being conducted on solutions to address the environmental pollution problems caused by these polymer materials. One such method involves replacing existing petroleum-derived polymers with biodegradable polymer materials.

[0004] Biodegradable plastics can be broken down into water, carbon dioxide, and biomass through the action of living organisms. Consequently, there is an increasing social demand to prevent environmental pollution caused by petroleum-derived plastics, and the biodegradable plastic market continues to show strong growth. Among these, packaging and containers account for approximately 61% of the total biodegradable plastic market.

[0005] However, research to replace packaging sealing adhesives with biodegradable materials is not yet actively underway, and there are not many research and development results, particularly regarding biodegradable hot melt adhesives (HMAs).

[0006] Hot melt adhesives are one of the solvent-free, eco-friendly adhesives, and because they exhibit adhesion on various substrates, they are used in many fields such as packaging, automobiles, electronics, and clothing.

[0007] However, hot melt adhesives are generally manufactured using non-biodegradable polymers such as EVA, polyolefin, and styrene block copolymer, and thus are not meeting the market's demand for eco-friendly products. The problem to be solved

[0008] The present invention aims to solve the problems described above by providing a hot melt adhesive that is biodegradable and a method for manufacturing the same, while having the advantages of being able to adhere to various materials without the need for a solvent and being easily applicable, similar to conventional hot melt adhesives. means of solving the problem

[0009] The present invention provides a biodegradable hot melt adhesive comprising maleic oxide PBAT.

[0010] The above maleated PBAT can be prepared by heating and mixing a radical initiator and maleic anhydride with PBAT resin and grafting maleic acid onto the molten PBAT chains for a short reaction time.

[0011] The above maleated PBAT may be grafted with maleic acid in an amount of 0.07 to 0.18%, preferably 0.12 to 0.16%. If the content of maleic acid grafted onto the PBAT is below the above range or exceeds the above range, the adhesive strength is reduced.

[0012] The biodegradable hot melt adhesive containing maleic oxide PBAT according to the present invention may further include one or more additives selected from the group consisting of tackifiers, tack modifiers, antioxidants, plasticizers, pigments, and fillers, so that the tackiness, thermal stability, color, and mechanical strength of the hot melt adhesive can be controlled.

[0013] The present invention provides a method for manufacturing a biodegradable hot melt adhesive comprising maleated PBAT, comprising the steps of: mixing a PBAT resin, maleic acid, and an initiator to prepare a mixture; and heating and mixing the mixture to graft maleic acid onto the PBAT, wherein the mixture may comprise 1 to 7 parts by weight of maleic acid and 0.1 to 0.7 parts by weight of an initiator per 100 parts by weight of PBAT resin, and preferably may comprise 5 parts by weight of maleic acid and 0.5 parts by weight of an initiator per 100 parts by weight of PBAT resin.

[0014] In the method for manufacturing a biodegradable hot melt adhesive comprising maleic oxide PBAT according to the present invention, the step of heating and mixing the mixture to graft maleic acid onto the PBAT can be performed at 185 to 195 degrees for 7 to 13 minutes. Effects of the invention

[0015] The biodegradable hot melt adhesive containing maleic oxide PBAT according to the present invention has biodegradability similar to PBAT but possesses significantly improved adhesive strength compared to PBAT, so it can be used as an adhesive for various products requiring biodegradability, and in particular, it can be utilized as an adhesive required for the manufacture of packaging papers and packaging containers made of biodegradable resins and for products using said packaging papers and packaging containers. Brief explanation of the drawing

[0016] Figure 1 shows the ATR-FTIR spectra for the embodiments and comparative examples according to the present invention. (a) and (b) show the results before purification, and (c) and (d) show the results after purification. Figure 2 shows the results of measuring dynamic rheological properties, including (a) storage modulus, (b) loss modulus, (c) complex viscosity, and (d) tan δ vs. angular frequency. Figure 3a) shows the Van Gurp-Palmen plot and (b) shows the Cole-Cole plot, measured at 160 degrees. Figure 4 shows the frequency sweep curves and cross-over points measured at 160 degrees. Figure 5 shows the TGA measurement results. Figure 6 shows the results of the adhesion test, where (a) and (c) show the Lap shear strength, and (b) and (d) show the Lap shear strength and displacement. Figure 7 shows the results of evaluating the biodegradability of cellulose, PBAT, and maleated PBAT according to Example 3. Specific details for implementing the invention

[0017] The terms used in this specification are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. As used in this specification, "comprises" does not exclude the presence or addition of one or more other components in addition to the components mentioned.

[0018] Unless otherwise defined, all terms used herein (including technical and scientific terms) may be used in a meaning commonly understood by those skilled in the art to which the present invention pertains. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise.

[0020] The biodegradable hot melt adhesive comprising maleic oxide PBAT according to the present invention comprises maleic oxide PBAT.

[0021] The above maleated PBAT can be prepared by grafting maleic anhydride onto molten PBAT chains for a short reaction time using a radical initiator. As the content of maleic anhydride and initiator added during the reaction process increases, the adhesive strength and melt viscosity of the maleated PBAT improve.

[0022] The above maleic oxide PBAT may be used in which maleic acid is grafted at 0.07 to 0.18%, preferably 0.12 to 0.16%, and if the content of maleic acid grafted onto the PBAT is below the above range or exceeds the above range, the adhesive strength is reduced.

[0023] The biodegradable hot melt adhesive containing maleic oxide PBAT according to the present invention may additionally include one or more additives selected from the group consisting of tackifiers, tack modifiers, antioxidants, plasticizers, pigments, and fillers, in addition to maleic oxide PBAT.

[0024] By adjusting the above additives, the tackiness, thermal stability, color, and mechanical strength of the hot melt adhesive can be controlled.

[0025] A biodegradable hot melt adhesive comprising maleic oxide PBAT according to the present invention can be manufactured by a manufacturing method comprising the steps of: mixing a PBAT resin, maleic acid, and an initiator to prepare a mixture; and heating and mixing the mixture to graft maleic acid onto the PBAT, wherein the mixture may comprise 1 to 7 parts by weight of maleic acid and 0.1 to 0.7 parts by weight of initiator per 100 parts by weight of PBAT resin, and preferably may comprise 5 parts by weight of maleic acid and 0.5 parts by weight of initiator per 100 parts by weight of PBAT resin.

[0026] In the method for manufacturing a biodegradable hot melt adhesive comprising maleic oxide PBAT according to the present invention, the step of heating and mixing the mixture to graft maleic acid onto the PBAT can be performed at 185 to 195 degrees for 7 to 13 minutes.

[0028] The following describes in detail, through embodiments of the present invention, a biodegradable hot melt adhesive containing maleic oxide PBAT, a method for manufacturing the same, and the adhesive strength and biodegradability of the biodegradable hot melt adhesive containing maleic oxide PBAT, so that a person skilled in the art to which the present invention pertains can easily practice the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0030] 1. Manufacture of Maleic Oxide PBAT Hot Melt Adhesive

[0031] Poly(Butylene-co-Adipate Terephthalate, PBAT A400) from Kingfa Sci. & Tech. Co., Ltd. (Guangzhou, China) was dried in a vacuum oven at 50°C for 12 hours.

[0032] After drying, PBAT, maleic anhydride from Sigma-Aldrich (≥99.0%, MA), and an initiator from Nouryon Co., Ltd. (2,5-Dimethyl-2,5-di(tert-butylperoxy) hexane, Trigonox®) were mixed in the compositional ratios as disclosed in Table 1.

[0033] The above mixture was introduced into a reactive mixer (Brabender® GmbH & Co. KG) and mixed and reacted at 190°C and 50 rpm for 10 minutes.

[0034] After the above reaction, the generated reaction product was cooled in a freezer at -20°C. After cooling, the reaction product was placed in a mold and processed at 160°C and 2 psi using a hot press to form a film with a thickness of 1 mm.

[0035] number sign PBAT(g) MA(g) Initiator (g) Comparative Example 1 Pristine 30 0 0 Comparative Example 2 ini-Pristine 30 0 0.15 Comparative Example 3 MA-Pristine 30 1.5 0 Example 1 MA1 30 0.3 0.03 Example 2 MA3 30 0.9 0.09 Example 3 MA5 30 1.5 0.15 Example 4 MA7 30 2.1 0.21

[0036] 2. Analysis of Biodegradable Maleic Oxide PBAT Hot Melt Adhesive

[0037] Spectroscopic Analysis

[0038] ATR-FTIR spectra for the above-prepared film were performed at room temperature on a Nicolet iS20 (Thermo Fisher Scientific, Waltham, MA, USA). Measurements were taken with 16 scans at a resolution of 4 Kaiser, and each spectrum was obtained within the range of 4000–525 Kaiser.

[0039] As shown in Figure 1, peaks at wavelengths of approximately 1,762 and 1,835 Kaiser could be observed in all cases where maleic acid was added. These are peaks caused by the symmetric (strong) and asymmetric (weak) C=O stretching vibrations of maleic acid, as is well known. The peak observed around 675 Kaiser is a peak for the C=C bond stretching of maleic acid, and the intensity of the peak increased as the amount of added maleic acid increased.

[0040] Among them, Comparative Example 3 (MA-Pristine), to which only maleic acid was added, was found to have the highest strength (see Fig. 1(b)). This result is because unreacted maleic acid remains in all films to which maleic acid was added.

[0041] Therefore, it was confirmed that no peaks were observed in the corresponding wavelength range when the unreacted maleic acid was removed from the film and the ATR-FTIR spectrum was measured (see Figure 1 (c) and (d)). In addition, in the spectrum after removing the unreacted maleic acid, the intensity of the peaks due to the C=O stretching vibrations of maleic acid decreased, but the intensity order between the PBAT grafted with maleic acid remained the same as before.

[0042] The content of maleic acid grafted on PBAT was quantified through titration and calculated using the formula below, and the results are shown in Table 2.

[0044] Grafting rate(%)=(W grafted / W initial )×100

[0046] Consequently, the results of the analysis via IR were consistent with the maleic acid content of maleated PBAT calculated through titration conducted in the same manner as Shao-Jun et al. (ACS Sustainable Chemistry & Engineering 2020 8 (13), 5338-5346).

[0047] number sign MA grafting rate (%) Mn(g / mol) Mw(g / mol) PDI Comparative Example 1 Pristine 0.00 68,325 157,520 2.31 Comparative Example 2 ini-Pristine 0.00 60,318 226,747 3.76 Comparative Example 3 MA-Pristine 0.04 74,474 159,434 2.14 Example 1 MA1 0.07 78,272 200,759 2.57 Example 2 MA3 0.09 75,568 213,505 2.83 Example 3 MA5 0.15 73,092 226,804 3.10 Example 4 MA7 0.18 70,438 234,159 3.32

[0048] <Molecular Weight and Polydispersity Index>

[0049] To determine the molecular weights of pure PBAT and maleated PBAT, gel permeation chromatography (GPC) was performed using standard polystyrene at 35°C in an Alliance e2695 separation module (Waters, Milford, MA, USA). The retention time was 30 minutes, and chloroform was used as the solvent. The results are shown in Table 2.

[0050] GPC analysis results confirmed that the molecular weight of PBAT changes as it reacts with maleic acid and an initiator. In the case of maleated PBAT, the Polydispersity Index (PDI) increased as the amounts of maleic acid and initiator reacting with PBAT increased. This is attributed to the fact that not only maleic acid grafting but also β-scission of the PBAT chain occurs during the reaction. When polymer chains possessing radical sites generated by β-scission attack other polymer chains, branching occurs in the attacked polymer chains. Consequently, it is believed that the PDI increased as this process was repeated during the reaction. The degree of increase in PDI was found to be proportional to the amount of initiator added. However, the highest PDI was observed in Comparative Example 2 (ini-Pristine), in which only the initiator was reacted. This is attributed to the fact that since maleic acid was not added, the process of maleic acid grafting did not occur during the reaction, allowing the greatest amount of β-scission to take place during the reaction time. This can also be confirmed through the torque change curve according to reaction time.

[0052] Rheological properties

[0053] Dynamic rheological properties were measured using a Discovery HR20 rheometer (TA Instrument, USA) with parallel plates (25 mm, 1 mm spacing). During the measurements, a strain sweep was performed at 160°C, a frequency of 1 Hz, and a strain range of 0.005–500 rad / s. A frequency sweep was performed at 160°C, a strain of 1%, and a frequency range of 0.01–628 rad / s. The flow temperature ramp was 1 s -1 The temperature was carried out from 115°C to 195°C at a shear rate and ramp rate of 5°C / min.

[0054] The above measurement results are shown in Figure 2.

[0055] Compared to pure PBAT (see Comparative Example 1, Pristine), increased shear-thinning behavior was observed for storage modulus (G'), loss modulus (G''), and complex viscosity (η*) as the amounts of added maleic acid and initiator increased (see Figures 2(a), (b), and (c)). Similarly, it was confirmed that the tan δ of all maleated PBAT samples was lower than that of PBAT (see Figure 2(d)). This phenomenon was observed only in the samples with added initiator. Therefore, it can be seen that structural changes in the PBAT chains occurred due to the initiator during the reaction.

[0056] To verify the structural changes of maleated PBAT, a Van Gurp-Palmen plot was examined (see Fig. 3(a)). PBAT without added initiator (Comparative Example 1) and MA-Pristine (Comparative Example 3) exhibited curves similar to those of typical linear polymers. As the phase angle decreased, MA-Pristine (Comparative Example 3) had a lower complex modulus (G*) than pristine PBAT (Comparative Example 1). This is thought to be due to the influence of unreacted maleic acid.

[0057] On the other hand, all samples reacted with an initiator exhibited different curve shapes. The curve shape, which shows a reduced phase angle unlike linear polymers, can be attributed to the influence of complex structures formed by long chain branches (LCBs). This is because the β-scission caused by the initiator added during the reaction generates long chain branch structures, which can increase chain entanglement.

[0058] To further investigate the influence of molecular structure, the relationship between dynamic viscosity (η′) and imaginary viscosity (η′′) was examined using a Cole-Cole plot (see Fig. 3(b)). As a result, the sample without added initiator exhibited a semicircular curve, which is consistent with the behavior of a typical linear polymer. In contrast, the sample with added initiator showed a curve with an increased radius, implying that a larger radius indicates the longest relaxation time. Additionally, it is generally known that the radius of the curve increases as the molecular weight increases.

[0059] However, when comparing the respective Mn and Mw in Table 2, MA5 (Example 3) showed the largest radius curve even though it did not have the largest Mn and Mw. Furthermore, when checking the cross-over point of the G' and G” curves of each specimen in Fig. 4, it can be confirmed that MA5 (Example 3) shows the cross-over point at the lowest angular frequency.

[0060] Looking at the reasons for these results, it can be observed that the curve radius size in the Cole-Cole plot, the intersection of G' and G”, and the Mw in the GPC results show nearly similar trends. However, only in the case of Mw, MA7 has a higher Mw than MA5. The fact that MA5 (Example 3) appears to have the largest molecular weight in the dynamic rheological property analysis results seems to be the result of increased chain entanglement caused by the formation of a more complex structure through long chain branches. Previous studies have also reported that a lower crossover frequency is associated with a longer relaxation time, which may support the presence of more branched polymers.

[0061] The structural influence of these polymer chains was also confirmed in the melt viscosity. As a result of measuring the melt viscosity according to temperature, all maleic oxide PBATs showed higher melt viscosity than pristine PBAT (Comparative Example 1) in the temperature range above the melting point. Among them, MA5 (Example 3) showed the highest melt viscosity. This is believed to be because, as can be seen from the previous results, the chain entanglement increases due to long chain branching, resulting in higher melt viscosity.

[0063] <Evaluation of Thermal Properties>

[0064] The thermal stability and unreacted maleic anhydride content of each sample were measured using a TGA55 thermogravimetric analyzer (TA Instruments, USA) at temperatures ranging from 30 to 600°C, a heating rate of 20°C / min, and a dry nitrogen gas flow rate of 40 mL / min. Crystallization and melting behaviors were also measured using differential scanning calorimetry (DSC). Using a DSC25 (TA), the first heating was performed from room temperature to 180°C at a rate of 10°C / min, the first cooling from 180°C to -70°C at a rate of 10°C / min, and the second heating from -70°C to 180°C at a rate of 10°C / min. The isothermal process was maintained for 5 minutes between each step, and all DSC scans were performed under a nitrogen atmosphere.

[0065] Figure 5 shows the TGA measurement results conducted under a nitrogen atmosphere. Since only a portion of the maleic acid added during the grafting process participates in the reaction, unreacted maleic acid remains in the maleated PBAT. Weight loss was assessed for each specimen at 202 °C, the boiling point of maleic acid. Pristine PBAT (Comparative Example 1) showed a loss of approximately 0.08%, while maleated PBAT exhibited higher weight loss as the amounts of maleic acid and initiator increased. Among all samples, MA-Pristine (Comparative Example 3) showed the highest weight loss. This is because only a small amount of maleic acid is grafted since no initiator is added, resulting in the presence of a large amount of unreacted maleic acid; this aligns well with the IR analysis results (see Figure 1(b)). Regarding the 5% decomposition temperature, Pristine PBAT exhibited a 5% decomposition temperature of approximately 340.56 °C. On the other hand, maleic oxide PBAT has a 5% decomposition temperature at a lower temperature. This result is due to an increase in the weight of residual maleic acid relative to the total sample weight.

[0066] The measurement results of crystallization and melting behavior for each specimen are shown in Table 3.

[0067] number sign Tg(degrees) Tc(do) Tm(degrees) Degree of crystallization (%) Half width of Tc (degrees) Crystallization onset temperature (degrees) Comparative Example 1 Pristine -30.42 66.32 121.21 14.92 9.53 75.46 Comparative Example 2 ini-Pristine -31.31 86.68 124.43 11.51 14.9 96.06 Comparative Example 3 MA-Pristine -31.40 69.45 121.13 13.81 10.55 80.6 Example 1 MA1 -29.58 66.26 119.31 14.18 10.36 75.04 Example 2 MA3 -27.85 61.24 118.76 13.97 9.76 72.89 Example 3 MA5 -26.71 62.09 118.08 13.11 9.11 72.11 Example 4 MA7 -24.89 64.91 117.19 13.52 9.30 73.22

[0068] The Tg, Tc, and Tm of pristine PBAT (Comparative Example 1) were -30.42°C, 66.32°C, and 121.2°C, respectively. However, the maleated PBAT samples exhibited different characteristics. First, regarding the crystallization temperature (Tc), it can be seen that maleated PBAT has a lower Tc compared to pristine PBAT (Comparative Example 1). This is because crystallization becomes more difficult as chain movement is restricted due to increased chain entanglement caused by the complex long chain branches (LCBs) structure present in maleated PBAT.

[0069] Looking at the crystallization onset temperature (Tc, onset), it can be seen that the maleic oxide PBAT is lower than the pristine PBAT (Comparative Example 1), just like Tc. However, the reason why MA5 (Example 3) has a lower crystallization onset temperature than MA7 (Example 4) is judged to be because there is more chain entanglement in MA5 (Example 3). This effect was confirmed by the fact that the degree of crystallization calculated through the crystallization peak also showed similar results.

[0070] On the other hand, the fact that MA1 (Example 1) shows a slightly higher Tc than pristine PBAT (Comparative Example 1) is because, as can be seen from the dynamic rheological property analysis confirmed earlier, MA1 has relatively less chain entanglement compared to other maleated PBATs. Therefore, since MA1 has less chain entanglement, it can be seen that the branched polymer chains generated during the reaction actually aid in crystallization, resulting in this outcome.

[0071] Despite the decrease in crystallinity of all maleated PBATs, the glass transition temperature (Tg) increased with increasing maleic acid and initiator content. This is because the movement of chains is more restricted when they move into the crystal lattice or other spaces due to the presence of LCB structures and the increased chain entanglement generated from those structures. Through this, it can be confirmed that chain entanglement played a more dominant role than crystallinity in determining Tg.

[0072] Similarly, the reason the Tm of maleated PBAT decreases compared to pristine PBAT (Comparative Example 1) is that the degree of crystallization and the perfection of the crystalline region of maleated PBAT decrease due to the LCBs structure.

[0073] MA-Pristine (Comparative Example 3) and ini-Pristine (Example 2) also exhibited different crystallization and melting behaviors (see Table 3). In the case of MA-Pristine (Comparative Example 3), the degree of crystallization and Tm decreased, but Tg increased. This can be attributed to unreacted maleic acid acting as a plasticizer, and this effect was also confirmed through dynamic rheological analysis results (see Fig. 2). On the other hand, Tc increased compared to pristine PBAT (Comparative Example 1), which can be attributed to maleic acid acting as a nucleating agent.

[0074] Comparative Example 2 (ini-Pristine) also showed an increased Tc. This is likely because there is less chain entanglement and a large amount of chains with a structure that can aid crystallization. In the case of ini-Pristine (Comparative Example 2), increased Tg and Tm compared to pristine PBAT (Comparative Example 1) can also be observed. This is judged to be because a small amount of gel was formed within the structure of ini-Pristine (Comparative Example 2), as a cross-linking reaction occurs when only peroxide is added to PBAT.

[0076] 3. Evaluation of Adhesion Strength of Maleic Oxide PBAT Hot Melt Adhesive

[0077] The films prepared according to Comparative Examples 1–3 and Examples 1–4 were cut into rectangular shapes (25 mm × 12.5 mm). Two stainless steel substrates (100 mm × 25 mm × 1.5 mm) were overlapped so that the film was placed between them. The overlapping area of ​​the two substrates was equal to the total area of ​​the film. Then, the film and the two substrates were secured together with two paper clips and left in a 130°C oven for 20 minutes. After removing the paper clips securing the samples and cooling them at room temperature for 24 hours, the adhesion strength was evaluated using a single lap shear test with an ST-1001 electronic universal testing machine. The evaluation was performed at a tensile speed of 1.3 mm / min, and five samples were evaluated per specimen, with the results presented as the average.

[0078] As shown in Fig. 6, the results of the single lap shear test showed that pristine PBAT (Comparative Example 1) exhibited an adhesion strength of 0.95±0.384 MPa (see Fig. 6 (a) and (b)), and all maleic oxide PBATs showed higher adhesion strength than pristine PBAT (Comparative Example 1). Among them, MA5 (Example 3) showed the highest value at 3.56±0.174 MPa. MA-Pristine (Comparative Example 3) and ini-Pristine (Comparative Example 2) showed values ​​of 2.01±0.363 and 1.44±0.299 MPa, respectively. Through this, it was confirmed that both specimens had adhesion strengths higher than pristine PBAT but lower than MA5 (Example 3). The reason for these results is that, first, in the case of MA-Pristine (Comparative Example 3), the interaction with the substrate and wettability were increased due to the maleic acid grafted on the main chain (see Table 2), which is believed to have resulted in improved adhesion strength compared to pristine PBAT (Comparative Example 1). According to previous studies, maleic anhydride can form chemical bonds with substrates containing hydroxyl groups.

[0079] On the other hand, ini-Pristine (Comparative Example 2) showed higher adhesive strength than pristine PBAT (Comparative Example 1) even though maleic acid was not present. This is because the initiator can form chains having LCBs that can increase chain entanglement within the ini-Pristine structure. The increase in chain entanglement leads to an increase in cohesive energy between chains, which is believed to result in improved adhesive strength.

[0080] Consequently, when only maleic acid is added, as previously confirmed through ATR-FTIR or GPC analysis results, some of the added maleic acid can be grafted onto the PBAT chain, thereby increasing the adhesive strength, similar to maleic oxide PBAT. However, when reacted with an initiator, it is judged that not only is the amount of grafted maleic acid increased, but LCBs structures can also be formed, resulting in higher adhesive strength. In the case of Example 3 (MA5), a relatively large amount of maleic acid is grafted, and at the same time, because it has the most complex LCBs structure among all maleic oxide PBATs, it is judged that MA5 (Example 3) exhibits adhesive strength similar to or higher than MA7 (Example 4), even though the largest amount of maleic acid is not grafted.

[0082] 4. Evaluation of Biodegradability of Maleic Oxide PBAT Hot Melt Adhesive

[0083] The aerobic biodegradation of Pristine PBAT (Comparative Example 1) and maleated PBAT (MA5, Example 3) was evaluated through a controlled composting test in accordance with ISO 14855-1 (2012). The inoculum consisted of stabilized and mature compost derived from the organic matter of municipal solid waste. The incubation temperature was maintained at 58 ± 2°C, and during the aerobic biodegradation of organic matter, a gas mixture (mainly carbon dioxide and water vapor) was the final degradation product, while some of the organic matter was assimilated for cell growth.

[0084] To confirm the biodegradability of biodegradable plastics due to hydrolysis and aerobic microorganisms, a quantitative analysis of carbon dioxide generated during the biodegradation process was performed, and the results are shown in Fig. 7. According to the guidelines of the ISO 14855-1 test method, the results are valid when the biodegradability of the standard material (cellulose) exceeds 70% over 45 days. In the evaluation performed, the standard material was confirmed to have a biodegradability of 87.98±5.8% over 50 days, so the evaluation results can be considered valid. Pristine PBAT (Comparative Example 1) showed a biodegradability of 87.78±1.8% over 50 days, which corresponds to 99.77% of the biodegradability of the standard material. Maleated PBAT (MA5, Example 3) showed a biodegradability of 85.57±1.7% over 50 days, which corresponds to 97.26% of the biodegradability of the standard material.

[0085] Maleated PBAT (Example 3) showed a slightly lower degree of biodegradability than pristine PBAT (Comparative Example 1) due to the LCBs structure formed during the reaction with grafted maleic acid. However, it is determined that this does not affect the intrinsic biodegradability of PBAT.

[0087] Therefore, the biodegradable hot melt adhesive containing maleic oxide PBAT according to the present invention can be used as a biodegradable hot melt adhesive because it possesses improved adhesive strength while maintaining biodegradability almost similar to that of PBAT.

[0088] In addition, although the above-described examples describe a biodegradable hot melt adhesive containing maleic oxide PBAT, the hot melt adhesive containing maleic oxide PBAT according to the present invention can be manufactured into a biodegradable hot melt adhesive containing maleic oxide PBAT resin by using it together with one or more additives selected from the group consisting of tackifiers, tack modifiers, antioxidants, plasticizers, pigments, and fillers.

[0089] One or more selected from rosin ester resins, rosin resins, terpene resins, petroleum resins, and oil-soluble phenolic resins may be used as the tackifier, and the tackifier may be selected from the group consisting of valeric acid amide, myristic acid amide, palmitic acid amide, arachidonic acid amide, behenic acid amide, erucic acid amide, stearic acid amide, oleic acid amide, and mixtures thereof.

[0090] By controlling the type and content of the above additives, the tackiness, thermal stability, color, and mechanical strength of the biodegradable hot melt adhesive containing maleic oxide PBAT can be controlled.

Claims

Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A method for manufacturing a biodegradable hot melt adhesive comprising maleated PBAT, comprising the steps of: mixing a PBAT resin, maleic acid, and an initiator to prepare a mixture; and heating and mixing the mixture to graft maleic acid onto the PBAT, wherein the mixture comprises 5 parts by weight of maleic acid and 0.5 parts by weight of an initiator per 100 parts by weight of PBAT resin, the step of heating and mixing the mixture to graft maleic acid onto the PBAT is performed at 185 to 195 degrees for 7 to 13 minutes, and the maleated PBAT is characterized by having 0.12 to 0.16% maleic acid grafted thereon. Claim 6 delete

Citation Information

Patent Citations

  • Biodegradable hot-melt adhesive composition

    KR1020230094355A

  • Biodegradable compositiom and biodegradable film

    KR1020230170586A

  • Biocomposites based on biodegradable polymers

    KR1020240037995A

  • Biodegradable hot melt adhesive material for packaging and manufacturing method thereof

    KR1020240076529A

  • Acid-modified polyester resin composition and laminate

    JP2024046111A